2020
DOI: 10.1002/tox.22913
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise and eugenol supplementation ameliorated liver injury induced by chlorpyrifos via modulation acetylcholinesterase activation and antioxidant defense

Abstract: The primary metabolize of chlorpyrifos (CPF) is in the liver tissue, which it can cause oxidative damage and apoptosis in liver cells. The use of exercise with antioxidant supplements could have a protective effects in the liver tissue especially by improve mitochondria function. The aim of the present study was to investigate the protective effect of aerobic exercise and eugenol (Eu) supplementation on destructive effects of CPF in liver tissue. Sixty-four adult male albino rats were randomly divided into eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Indeed, these two proposals can explain the reduction observed in the EDL muscle AChE activity. Not surprisingly, ours results agree to the others authors that observed reduction (Kaufer et al, 1998;Jasmin & Gisiger, 1990;Nikbin et al, 2020) or no significant difference (Farzi et al, 2019) in the activity of AChE using different exercise protocols. Thus, in this preliminary work we have underpinned future studies that might investigate molecular changes related in these responses observed in AChE activity.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, these two proposals can explain the reduction observed in the EDL muscle AChE activity. Not surprisingly, ours results agree to the others authors that observed reduction (Kaufer et al, 1998;Jasmin & Gisiger, 1990;Nikbin et al, 2020) or no significant difference (Farzi et al, 2019) in the activity of AChE using different exercise protocols. Thus, in this preliminary work we have underpinned future studies that might investigate molecular changes related in these responses observed in AChE activity.…”
Section: Discussionsupporting
confidence: 93%
“…Exercise training is an effective intervention to improve cardiac function in MI patients [ 17 ]. It has been reported that exercise training provides beneficial effects in various liver diseases, including hepatic ischemia-reperfusion injury [ 18 ], drug-related liver injury [ 19 ], and non-alcoholic fatty liver disease (NAFLD) [ 20 ]. The mechanisms were related to inhibiting ROS and inflammation, regulating M1/M2 macrophages polarization, increasing β-oxidation and reducing intrahepatic fat content, hepatocyte autophagy, and apoptosis [ 18 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the duration of training was fixed at 20 minutes, and the intensity of training reached 16 m/minute on the first day and 26 m/min on the last day. To start training, warm-up and cool-down exercises were performed for 5 minutes at a speed of 7 m/min and 5 minutes at a speed of 5 m/ minute after the main training, respectively (18).…”
Section: Aerobic Exercise Programmentioning
confidence: 99%